GURU MODEL PENDIDIKAN HIDUP ROHANI PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA - Tibo, Paulinus (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2020)
The purpose of this study is to find out how teachers as an educational model in developing the spiritual life of students at the secondary school level. This research is motivated by the lack of guidance from parents and teachers, students also rarely pray both privately and pray together, as a result students are less interested in participating in spiritual activities. The method used in this study is qualitative research, namely by obtaining information through direct interviews, observations and documentation. To respond to these problems, the authors conducted interviews with teachers and students in Junior High Schools. Besides it, observation and documentation are needed to strengthen valid data or information. Research findings in Junior High Schools are that teachers have carried out their duties in guiding and growing students 'faith but students are less aware that what teachers do is developing students' spiritual lives through prayer, worship and the deepening of the Scriptures.